2016
DOI: 10.2217/imt-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Engineered T-Cell Therapy for Synovial Sarcoma

Abstract: Synovial sarcoma is a rare soft tissue sarcoma characterized by a t(X;18) translocation, which results in a SYT-SSX gene fusion. In the metastatic setting, chemotherapy has limited, durable efficacy prompting the necessity for new therapeutic modalities. One emerging new strategy involves T-cell-directed therapy such as tumor-infiltrating lymphocytes or the development of T cells that are genetically engineered to express a T-cell receptor against a cancer testis antigen. Of these approaches, engineered T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The burgeoning field of immuno-oncology has led to improvement in patient outcomes across a wide range of cancer types, with FDA approvals in melanoma, Merkel cell carcinoma, urologic malignancies, and non-small cell lung cancer, among others, in both the metastatic and adjuvant settings (5)(6)(7). The success of immune checkpoint inhibitors has led to considerable interest in evaluating immunotherapy for sarcomas (3,(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The burgeoning field of immuno-oncology has led to improvement in patient outcomes across a wide range of cancer types, with FDA approvals in melanoma, Merkel cell carcinoma, urologic malignancies, and non-small cell lung cancer, among others, in both the metastatic and adjuvant settings (5)(6)(7). The success of immune checkpoint inhibitors has led to considerable interest in evaluating immunotherapy for sarcomas (3,(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Patients were randomized 1:1 to three cycles of standard treatment consisting of ifosfamide 3 g/m 2 on days 1–3 and epirubicin 60 mg/m 2 on days 1–2 of every 21 days vs. histology-tailored chemotherapy, which was in SS high-dose ifosfamide 1 g/m 2 on days 1–14 of every 28 days [ 15 ••]. After a median follow-up of 12.3 months for the total study population ( n = 287), the projected DFS at 46 months was 62% (95% CI 48–77) in the standard chemotherapy group and 38% [ 21 ••, 22 , 23 – 26 , 27 •, 28 •, 29 , 30 – 37 , 38 •, 39 , 40 44 , 45 ••, 46 , 47 , 48 , 49 •, 50 , 51 , 52 •, 53 , 54 ] in the histotype-tailored chemotherapy group (stratified log-rank p = 0.004; hazard ratio 2.00, 95% CI 1.22–3.26; p = 0.006). Subgroup analysis indicated no preference for histology-tailored chemotherapy in the SS cohort (HR 1.85, 95% CI 0.69–5.22).…”
Section: Current Pharmacological Treatment Optionsmentioning
confidence: 99%
“…In the field of immunotherapy, the use of engineered T cells directed against the NY-ESO-1 cancer/testis antigen, which is expressed in 80% of SS patients, has been the most promising approach in SS in clinical testing so far [ 52 •]. Objective responses were reported in 4/6 heavily pre-treated, metastatic, NY-ESO-1-expressing SS patients treated with lymphodepleting preparative chemotherapy followed by autologous T cells transduced with an NY-ESO-1-reactive T cell receptor, including tumor regressions.…”
Section: Novel Treatment Options Under Developmentmentioning
confidence: 99%
“…One cancer testis antigen, NY-ESO-1 is highly prevalent in synovial sarcoma, and there are studies using ACT with objective responses observed. It remains investigational until the present moment, however [63].…”
Section: Second- and Third-line Therapiesmentioning
confidence: 99%